Security, Energy Efficiency, Routing Protocols and Algorithms Applied to Underwater Wireless Sensor Network - Kaschel-Carcamo, H (Institute of Electrical and Electronics Engineers Inc., 2021)
Currently, Underwater Wireless Sensor Networks (UWSN) have taken on great relevance since they have applications both in the military field and the protection of marine edges, but also in the field of research such as monitoring of seismic activity, the environment and exploration of the seabed among others. However, these networks present great challenges for the scientific community and researchers given the different factors that affect their correct operation, some of them being energy consumption, reliability, ocean noise, high interferences, security, etc. This work addresses security, energy efficiency, protocols and algorithms applied to UWSN. © 2021 IEEE.